1995
DOI: 10.1111/j.2042-3306.1995.tb04929.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conditioning and exercise type on serum creatine kinase and aspartate aminotransferase activity

Abstract: Summary In the first study, 5 mature, unconditioned, Thoroughbred geldings performed an initial submaximal exercise test (UC) prior to any conditioning and a final test (C) following 8 weeks conditioning. Serum creatine kinase (CK) and aspartate aminotransferase (AST) activity were measured before and for 72 h after exercise. Plasma lactate concentration [La−] was used as an indicator of exercise conditioning. Serum CK and AST activity remained increased above pre‐exercise levels from 0–24 h and 0–8 h post exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…In this study, elevated plasma AST and CK activities were indicative of muscle cell leakage in both OD80 and OD160. Horses that were conditioned for 8 weeks had attenuated increases in CK and AST activities during a submaximal exercise test (Siciliano et al 1995). The large variability in plasma CK activities between horses during OD160 suggests differences in fitness condition (Figs 6a,b), although fitness was not measured in this study.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, elevated plasma AST and CK activities were indicative of muscle cell leakage in both OD80 and OD160. Horses that were conditioned for 8 weeks had attenuated increases in CK and AST activities during a submaximal exercise test (Siciliano et al 1995). The large variability in plasma CK activities between horses during OD160 suggests differences in fitness condition (Figs 6a,b), although fitness was not measured in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Segundo Siciliano et al (1995) e Câmara e Silva et al (2007), o treinamento pode atenuar o aumento da atividade sérica de AST após exercício físico. Porém, conforme já citado, não foi possível na presente pesquisa confirmar que o treinamento físico reduz a magnitude do aumento de AST sérico após o exercício porque nenhuma avaliação clínica e laboratorial dos mesmos animais foi feita previamente ao treinamento de forma a ser comparada com os resultados obtidos após a prova realizada.…”
Section: Discussionunclassified
“…BOFFI et al (2002) found significantly higher blood CK activities in trained horses. Higher levels of CK and AST were found after endurance exercise (HARGREAVES et al, 2002) as well as after short, high intensity exercise (SICILIANO et al, 1995). Likewise, CHIARADIA et al (1998) found no change in CK and LDH activities during training, probably due to myocyte adaptation.…”
Section: Discussionmentioning
confidence: 93%